Linking K-12 STEM Pedagogy to Local Contexts: A Scoping Review of Benefits and Limitations - Holmes, Kathryn; Mackenzie, Erin; Berger, Nathan; Walker, Michelle (Frontiers in Education, 2021)
Student engagement and learning in science, technology, engineering, and mathematics (STEM) fields in primary and secondary schools is increasingly being emphasized as the importance of STEM skills for future careers is realized. Localized learning has been identified as a group of pedagogical approaches that may enhance learning in STEM by making the relevance of STEM clear to students and providing stronger connections to students’ lives and contexts. This paper reports on a scoping review that was conducted to identify the benefits and limitations of localized learning in primary and secondary school STEM disciplines. A secondary aim of the review was to identify strategies that increase the effectiveness of localized learning these disciplines. Following literature searches of four databases, 1923 articles were identified. Twenty-five studies met the inclusion criteria. Potential benefits of localized learning included increases in enjoyment of STEM, improvements in learning, more positive STEM career aspirations, and development of transferable skills. The main challenges of these pedagogical approaches were time restrictions and lack of community involvement. Strategies for enhancing the impact of localized pedagogy included professional development for teachers (in STEM content knowledge, integration of localized pedagogy, and capacity to address socio-scientific issues), integration of technology, whole-school implementation of the pedagogical approach, and integration of the wider community into STEM education. These findings provide support for localized learning as an effective pedagogical approach to enhance STEM learning in schools, while emphasizing the critical roles of teachers and communities in supporting students to realize the relevance of STEM in their lives.